2020
DOI: 10.1136/bmjgast-2019-000350
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of perioperative mortality from complicated peptic ulcer disease in Africa: systematic review and meta-analysis

Abstract: IntroductionIn 2013, peptic ulcer disease (PUD) caused over 300 000 deaths globally. Low-income and middle-income countries are disproportionately affected. However, there is limited information regarding risk factors of perioperative mortality rates in these countries.ObjectiveTo assess perioperative mortality rates from complicated PUD in Africa and associated risk factors.DesignWe performed a systematic review and a random-effect meta-analysis of literature describing surgical management of complicated PUD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…PU was considered not improved or further aggravated if gastroscopy showed that the ulcer area was not significantly shortened or further increased. [ 8 ] Total clinical efficacy was calculated as a ratio of (cured + improved)/total cases × 100% = total effective rate. Recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…PU was considered not improved or further aggravated if gastroscopy showed that the ulcer area was not significantly shortened or further increased. [ 8 ] Total clinical efficacy was calculated as a ratio of (cured + improved)/total cases × 100% = total effective rate. Recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple causes of peptic ulcers, with the most common being Helicobacter pylori infection and ingestion of medications, especially non-steroidal anti-inflammatory drugs (NSAIDs) [ 4 ]. Other risk factors for peptic ulcers include smoking and other chronic medical conditions, and studies have shown that peptic ulcers are also more common in low-income countries [ 5 , 6 ]. A physiological balance between the pepsin within gastric acid and the gastroduodenal defense system is necessary to protect the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence study of seven developed countries based on doctors' diagnoses showed a prevalent rate that ranged from 0.1 to 1.5 percent whereas the prevalent rate based on hospitalization was estimated to be 0.1 to 0.19 percent [2]. It is estimated that Peptic ulcer disease (PUD) claimed more than 300,000 lives worldwide in 2013 and its incidence in Africa is increasingly high [3]. The disease condition is as a result of an imbalance between the aggressive factors (acid and pepsin) and mucosal defense factors (blood flow and endogenous prostaglandins) [4] that maintain an equilibrium of the stomach.…”
Section: Introductionmentioning
confidence: 99%